Analisis Persepektif Bahasa Indonesia dalam Masyarakat - Sugiarti Sugiarti; Prety Ratna Sari; Sunarni Sunarni; Sendy Firmansyah (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
This study aims to analyze the views and attitudes of the community towards the use of Indonesian in everyday life, and to identify the factors that influence it from social, cultural, educational, and media aspects. Using a quantitative descriptive approach, data were collected through questionnaires, observations, and interviews with 10 respondents from the community who use Indonesian and regional languages. The results of the study indicate that Indonesian plays an important role as a national identity, a unifying tool, and a reflection of the nation's culture. However, the influence of globalization and the development of digital technology have caused a shift in language attitudes, marked by the increasing use of foreign languages ​​and slang in everyday communication. However, there is still a high level of awareness in some communities to use Indonesian properly and correctly. This study emphasizes the importance of strengthening language literacy through education and media so that Indonesian remains existent, adaptive, and dignified in the modern era.